Assessment of clinical parameters among patients with snake poison induced coagulopathy - S., Hariprasad; Sukhani, Neha (International Journal of Advances in Medicine, 2018)
Background: Snakes are poikilothermic carnivorous reptiles that have evolved the venomous apparatus for the purpose of procurement of food. Snake bite can result in local and systemic complications. Major systemic complications include acute renal failure, neurologic abnormalities requiring ventilator support and disseminated intravascular coagulation. Disseminated intravascular coagulation can result in serious life-threatening systemic complications like haemorrhage, infarction and even death if the treatment is delayed. The present study was undertaken to study the clinical profile of the snake bite patients who develop coagulopathy and to study the role of coagulation markers to evaluate the morbidity and mortality of snake bite victims. Methods: Hundred patients consecutively admitted with history of snakebite were studied. Patients who have developed local signs of envenomation due to snake bite were included in the study group. The coagulation profile was assessed by doing blood investigations. Results: In this study, patients who developed coagulopathy had prolonged hospital stay and requirement of more blood products transfusion causing increased morbidity. 43 patients (35.8%) had platelets less than 1 lakh and approximately hospitalized for 26 days sand INR was more than 1.5 in 112 patients (93.3%) and hospitalized for 22 days and they received fresh frozen plasma. The survival rate in this study was 86% followed by 13.3% deaths. Conclusions: Use of clinical and laboratory parameter evaluation needed to identify the coagulopathy very early to reduce the hospital stay and mortality.